The economies of Southeast Asia before and after the crisis - Tongzon, Jose L., 1951-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2002)
This updated and fully revised second edition provides a comprehensive examination of issues of paramount importance for Southeast Asian economies including: the economic implications of the 1997 Asian crisis for both older and newer members of ASEAN; the role of government and FDI in ASEAN economic growth and development; trade patterns with the US, Japan and the EU and the economic implications of China's accession to the WTO for ASEAN countries; the environmental consequences of industrialisation and growth; the emergence of economic growth triangles and their contribution to ASEAN growth and regional cooperation; the prospects and challenges of ASEAN economic cooperation before and after the crisis; and the key challenges facing ASEAN member countries in the aftermath of the crisis.
pt. 1. ASEAN economic development and cooperation before the crisis -- pt. 2. ASEAN external economic relations -- pt. 3. The 1997 Asian crisis and its aftermath -- pt. 4. Future ASEAN economic cooperation and challenges.
Includes bibliographical references and index.
Keywords: Southeast Asia -- Economic conditions; Southeast Asia -- Economic integration; Electronic books